Co-designing a methodology for workforce development during the personalisation of allied health service funding for people with disability in Australia - Kristen Foley; Stacie Attrill; Chris Brebner (BMC, 2021)
Abstract Background Internationally, health and social services are undergoing creative and extensive redesign to meet population demands with rationed budgets. This has critical implications for the health workforces that serve such populations. Within the workforce literature, few approaches are described that enable workforce development for health professions in the service contexts that emerge from large scale service redesign in times of industry shift. We contribute an innovative and robust methodology for workforce development that was co-designed by stakeholders in allied health during the personalisation of disability funding in Australia (the introduction of the National Disability Insurance Scheme). Methods In the context of a broad action research project, we used program logic modelling to identify and enact opportunities for sustainable allied health education and workforce integration amidst the changed service provision context. We engaged with 49 industry stakeholders across 92 research engagements that included interviews (n = 43), a workshop explicitly for model development (n = 8) and a Project Advisory Group (n = 15). Data from these activities were inductively coded, analysed, and triangulated against each other. During the program logic modelling workshop, we worked with involved stakeholders to develop a conceptual model which could be used to guide trial and evaluation of allied health education which was fit-for-purpose to emerging workforce requirements. Results Stakeholder interviews showed that drivers of workforce design during industry shift were that (1) service provision was happening in turbulent times; (2) new concerns around skills and professional engagement were unfolding for AHP in the NDIS; and (3) impacts to AHP education were being experienced. The conceptual model we co-designed directly accounted for these contextual features by highlighting five underpinning principles that should inform methodologies for workforce development and AHP education in the transforming landscape: being (1) pedagogically sound; (2) person- or family-centred; (3) NDIS compliant; (4) informed by evidence and (5) having quality for all. We use a case study to illustrate how the co-designed conceptual model stimulated agility and flexibility in workforce and service redesign. Conclusions Proactive and situated education of the emerging workforce during policy shift is essential to realise future health workforces that can appropriately and effectively service populations under a variety of changing service and funding structures - as well as their transitions. We argue that collaborative program logic modelling in partnership with key stakeholders including existing workforce can be useful for broad purposes of workforce (re)design in diverse contexts.